A new twist on an old ligand: a [Mn16] double square wheel and a [Mn10] contorted wheel. Issue 7 (10th February 2021) - Tziotzi, Thomais G.; Coletta, Marco; Gray, Mark; Campbell, Cameron L.; Dalgarno, Scott J.; Lorusso, Giulia; Evangelisti, Marco; Brechin, Euan K.; Milios, Constantinos J.
Abstract : The use of 1, 3, 5-tri(2-hydroxyethyl)-1, 3, 5-triazacyclohexane (LH3 ) in manganese cluster chemistry leads to the synthesis of a Mn16 double square wheel and a Mn10 contorted wheel. Abstract : Ligand design remains key to the synthesis of coordination compounds possessing specific topologies, nuclearities and symmetries that direct targeted physical properties. N, O-chelates based on ethanolamine have been particularly prolific in constructing a variety of paramagnetic 3d transition metal complexes with fascinating magnetic properties. Here, we show that combining three ethanolamine moieties within the same organic framework in the form of the pro-ligand 1, 3, 5-tri(2-hydroxyethyl)-1, 3, 5-triazacyclohexane (LH3 ) leads to the formation of two highly unusual Mn wheels. Reaction of Mn(NO3 )2 ·6H2 O with LH3 in basic methanolic solutions leads to the formation of [MnIII12MnII4(μ3 -O)6 (μ-OH)4 (μ3 -OMe)2 (μ-OMe)2 (L)4 (LH)2 (H2 O)10 ](NO3 )6 (OH)2 (1 ) and [MnIII10(μ3 -O)4 (μ-OH)4 (μ-OMe)4 (L)4 (H2 O)4 ](NO3 )2 (2 ), the only difference in the synthesis being the ratio of metal:ligand employed. The structure of the former describes two offset [MnIII6MnII2] square wheels, linked through a common centre, and the latter a single [MnIII10] wheel twisted at its centre, such that the top half is orientated perpendicular to the bottom half. In both cases the L 3− /LH 2− ligands dictate the orientation of the Jahn-Teller axes of the Mn III ions which lie perpendicular to the triazacyclohexane plane. Direct current magnetic susceptibility and magnetisation data reveal the presence of competing exchange interactions in 1 and strong antiferromagnetic interactions in 2 . Given the simplicity of the reactions employed and the paucity of previous work, the formation of these two compounds suggests that LH3 will prove to be a profitable ligand for the synthesis of a multitude of novel 3d transition metal complexes.